Survival of ancient landforms in a collisional setting as revealed by combined fission track and (U-Th)/He thermochronometry: A case study from Corsica (France) - Danisik, Martin; Kuhlemann, J.; Dunkl, I.; Evans, Noreen; Szekely, B.; Frisch, W. (University of Chicago Press, 2012)
The age of high-elevation planation surfaces in Corsica is constrained using new apatite (U-Th)/He data, field observations, and published work (zircon fission track, apatite fission track [AFT] data and landform/stratigraphical analysis). Thermal modeling results based on AFT and (U-Th)/He data, and the Eocene sediments uncomformably overlapping the Variscan crystalline basement indicate that present-day elevated planation surfaces in Corsica are the remnants of an erosion surface formed on the basement between ∼120 and ∼60 Ma. During the Alpine collision in the Paleocene-Eocene, the Variscan crystalline basement was buried beneath a westward-thinning wedge of flysch, and the eastern portion was overridden by the Alpine nappes. Resetting of the apatite fission track thermochronometer suggests an overburden thickness of >4 km covering Variscan Corsica. Protected by soft sediment, the planation surface was preserved. In the latest Oligocene to Miocene times, the surface was re-exposed and offset by reactivated faults, with individual basement blocks differentially uplifted in several phases to elevations of, in some cases, >2 km.Currently the planation surface remnants occur at different altitudes and with variable tilt. This Corsican example demonstrates that under favorable conditions, paleolandforms typical of tectonically inactive areas can survive in tectonically active settings such as at collisional plate margins. The results of some samples also reveal some discrepancies in thermal histories modeled from combined AFT and (U-Th)/He data. In some cases, models could not find a cooling path that fit both data sets, while in other instances, the modeled cooling paths suggest isothermal holding at temperature levels just below the apatite partial annealing zone followed by final late Neogene cooling. This result appears to be an artifact of the modeling algorithm as it is in conflict with independent geological constraints. Caution should be used when cross-validating the AFT and (U-Th)/He systems both in the case extremely old terrains and in the case of rocks with a relatively simple, young cooling history.